Ovarian carcinosarcoma (a literature review) - A. M. Beishembaev; K. I. Zhordania; E. D. Choi; A. A. Turkmenov; A. K. Moldobekova (IRBIS LLC, 2022)
Introduction. Despite that ovarian carcinosarcoma (OCS) is an extremely rare disease, it is of great medical and social importance by taking into account very high level of overall mortality, recurrence, metastasis, and economic costs.Aim: to summarize current data on various aspects of OCS.Materials and Methods. The search strategy for English written papers published in databases PubMed/MEDLINE, Scopus, Web of Science, Google Scholar was based on the following keyword queries: «ovarian carcinosarcoma», «etiology and pathogenesis», «epidemiology», «classification», «clinical picture», «diagnosis», «treatment». The search depth was limited within the years 2010-2022, by prioritizing the search depth within the last 5 years (2017-2022).Results. We found 48 articles in English, published from 2016 to 2022, of which 47 (97.9 %) articles were published within the last 5 years. Scientific data are represented by studies with a small patient sample and with low evidence base. The results of the analysis for identified publications showed a limited, fragmented and inconsistent scientific data both in terms of etiology, pathogenesis and treatment, as well as an impact of OCS stages, age and other risk factors on the likelihood of relapses.Conclusion. The lack of extensive clinical studies along with observed substantial number of controversial issues may be accounted for by OCS low prevalence and complex pathogenesis. Nevertheless, the results obtained during the generalization of scientific knowledge provide a realistic insight into the current state of global science about this medical and social disease and may be used to improve the diagnostics and treatment of OCS patients.